Central melanopsin projections in the diurnal rodent, Arvicanthis niloticus - Jennifer Lou Langel; Laura eSmale; Laura eSmale; Laura eSmale; Gema eEsquiva; Gema eEsquiva; Jens eHannibal (Frontiers Media S.A., 2015)
The direct effects of photic stimuli on behavior are very different in diurnal and nocturnal species, as light stimulates an increase in activity in the former and a decrease in the latter. Studies of nocturnal mice have implicated a select population of retinal ganglion cells that are intrinsically photosensitive (ipRGCs) in mediation of these acute responses to light. ipRGCs are photosensitive due to the expression of the photopigment melanopsin; these cells use glutamate and pituitary adenylate cyclase-activating polypeptide (PACAP) as neurotransmitters. PACAP is useful for the study of central ipRGC projections because, in the retina, it is found exclusively within melanopsin cells. Little is known about the central projections of ipRGCs in diurnal species. Here, we first characterized these cells in the retina of the diurnal Nile grass rat using immunohistochemistry (IHC). The same basic subtypes of melanopsin cells that have been described in other mammals were present, but nearly 25% of them were displaced, primarily in its superior region. PACAP was present in 87.7% of all melanopsin cells, while 97.4% of PACAP cells contained melanopsin. We then investigated central projections of ipRGCs by examining the distribution of immunoreactive PACAP fibers in intact and enucleated animals. This revealed evidence that these cells project to the suprachiasmatic nucleus, lateral geniculate nucleus (LGN), pretectum and superior colliculus. This distribution was confirmed with injections of cholera toxin subunit β coupled with Alexa Fluor 488 in one eye and Alexa Flour 594 in the other, combined with IHC staining of PACAP. These studies also revealed that the ventral and dorsal LGN and the caudal olivary pretectal nucleus receive less innervation from ipRGCs than that reported in nocturnal rodents. Overall, these data suggest that although ipRGCs and their projections are very similar in diurnal and nocturnal rodents, they may not be identical.